2018
DOI: 10.1101/420893
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dihydropyrimidinase protects from DNA replication stress caused by cytotoxic metabolites.

Abstract: Imbalance in the level of the pyrimidine degradation products dihydrouracil and dihydrothymine is associated with cellular transformation and cancer progression. Dihydropyrimidines are degraded by dihydropyrimidinase (DHP), a zinc metalloenzyme that is upregulated in solid tumors but not in the corresponding normal tissues. How dihydropyrimidine metabolites affect cellular phenotypes remains elusive. Here we show that the suppression of DHP in cancer cell lines is cytotoxic. An increase in the level of dihydro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Subsequent base-or nucleotide excision repair can lead to direct or indirect release of these dihydropyrimidines in cells (Venkhataraman et al 2001). Studies on cancer cells and on in vitro DNA replication in Xenopus egg extracts showed that dihydropyrimidines cause DNA-protein crosslinking, interfere with DNA replication and cause transcriptional stress (Basbous et al 2020). In mammalian cells, the zinc metalloprotein dihydropyrimidinase plays a key role in dihydropyrimidine detoxification (Brooks et al 1979;Kikugawa et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent base-or nucleotide excision repair can lead to direct or indirect release of these dihydropyrimidines in cells (Venkhataraman et al 2001). Studies on cancer cells and on in vitro DNA replication in Xenopus egg extracts showed that dihydropyrimidines cause DNA-protein crosslinking, interfere with DNA replication and cause transcriptional stress (Basbous et al 2020). In mammalian cells, the zinc metalloprotein dihydropyrimidinase plays a key role in dihydropyrimidine detoxification (Brooks et al 1979;Kikugawa et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…DPYS (also known as DHP) is a zinc metalloenzyme, which is highly expressed in tumors compared with the matching normal tissues, whose role is to degrade dihydropyrimidine [27]. Excessive accumulation of dihydropyrimidine will facilitate the constitution of DNA-protein crosslinks, leading to DNA replication and transcriptional stress [27]. Studies have shown that DPYS subtype DPYSL3 was a promising biomarker for GC malignant behavior [28].…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of NT5E can promote tumor proliferation, migration and invasion [25,26]. DPYS (also known as DHP) is a zinc metalloenzyme, which is highly expressed in tumors compared with the matching normal tissues, whose role is to degrade dihydropyrimidine [27]. Excessive accumulation of dihydropyrimidine will facilitate the constitution of DNA-protein crosslinks, leading to DNA replication and transcriptional stress [27].…”
Section: Discussionmentioning
confidence: 99%
“…In vitro spectroscopic studies have identified the strikingly high level of the thymine breakdown through the DHT pathway, leading to e.g. breast and lung adenocarcinomas [86][87][88][89]. Thus, it appears as tempting in Fig.…”
Section: Reconstructed Spectramentioning
confidence: 99%